Pharmacognostic and Preliminary Phytochemical Standardization of Tamarixaphylla and Ziziphusnummulariagrowing in Saudi Arabia - Yusufoglu, Hasan Soliman; Alam, Aftab; Al-Howeemel, Abdullah (Asian Journal of Biological and Life Sciences, 2015)
Tamarixaphylla (Family: Tamaracaceae), commonly known as Athil and farash an evergreen tree. The natives it used for treatment of jaundice, bad evils, rheumatism, wound and abscesses. Ziziphusnummularia (Family: Rhamnaceae), commonly known as Sidar or Jharber, is a thorny bush and shrub. It is used for wound and abscesses, scabies and other skin disease. These plants are widely used by Arabs.However,no detailed scientific information is available to identify and authenticate these local plants. In the present study,the macroscopical and microscopical characters along with physicochemical parameters and phytochemical screening were carried out in order to identify and authenticate the leaves of both plants. The physicochemical parameters such as moisture content,total ash,water-soluble, acid-insoluble ash and values of petroleum ether, alcohol and water extractives were documented for both the plants. The results of phytochemicals screening suggested that the active compounds present in both plants could be beneficial in treatment of various ailments.
Keywords: Anatomical; Morphological; Physico-chemical; Tamarixaphylla; Ziziphusnummularia